KORELASI FIKIH DAN SAINS DALAM PENENTUAN ARAH KIBLAT - Ardliansyah, Moelki Fahmi (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2017)
Today, the discussion of the direction of Qibla is not only focused on the jurisprudence aspect, other s ciences also contribute to the discussion of the direction of Qibla, such as astronomy, mathematics, geodesy, etc. as a manifestation of the development of the times also that the calculation of the direction of Qibla solved by various methods through the science of science, this is because the direction is the discussion of nature, and nature has a lot of concentration in various sciences, so the classical problems that occur in the fiqh, now clarified with the science of science. This paper aims to determine the correlation of jurisprudence and science in the determination of Qibla direction. The method used is descriptive-analysis and literature study. The conclusion of this paper is that there is a correlation of the science of jurisprudence and science in the application of the direction of qibla. Both can not be separated and interrelated with each other. Because fiqih is the foundation, while science is likened to a tool for berijtihad. Fiqh became the basis for the mujtahids to be able to find the law in facing Qiblah, while science answered the ways and methods to be able to face the Qibla that is not explained in the fiqh. Of the three theories of science studies above, trigonometric theory of the ball is the theory most often used. However, in the application of jurisprudence of jurisprudence according to the science of the closest theory is the theory of geodesy because it takes into account the real shape of the earth that is ellipsoid that is not just spherical ball.